The women, gender and development reader - Visvanathan, Nalini, 1945- (Fernwood Pub. ; Zed Books Ltd. ; Distributed in the USA exclusively by Palgrave Macmillan, 2011)
"In this fully revised second edition, the editors expertly present the impact of social, political and economic change by reviewing such topical issues as migration, persistent structural discrimination, the global recession and climate change. With a multidisciplinary approach, the volume vividly illustrates the theoretical debates with an array of case studies from around the world"--P. [4] of cover.